2019
DOI: 10.1111/jtxs.12391
|View full text |Cite
|
Sign up to set email alerts
|

In vitro digestion of bread: How is it influenced by the bolus characteristics?

Abstract: This study aimed to understand the impact of in vitro oral processing methods on bolus formation and the kinetics of starch hydrolysis of refined white bread during in vitro gastrointestinal digestion. Four in vitro oral processing methods (i.e., cut, cut‐and‐pestle, blend, and grind) were performed at two levels of disintegration (less and more intensive) and compared with human mastication. Boluses prepared using the in vitro methods had a larger particle size (20–69 mm2 vs. 14 mm2), a higher moisture conten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 45 publications
1
13
1
Order By: Relevance
“…However, there is not a direct relationship between food chemical composition and these effects on health because alterations in food matrix structures lead to differences in nutrient bioavailability, rates of absorption and post-prandial outcomes that might modify their potential health risks [4]. Additionally, the breakdown of the food matrix during the digestion process affects the rate at which foods are digested [5]. Therefore, clear attention should be given to the food matrix structure as well as to the food digestive process in order to understand how to control the glycemic index of carbohydrate-rich foods.…”
Section: Introductionmentioning
confidence: 99%
“…However, there is not a direct relationship between food chemical composition and these effects on health because alterations in food matrix structures lead to differences in nutrient bioavailability, rates of absorption and post-prandial outcomes that might modify their potential health risks [4]. Additionally, the breakdown of the food matrix during the digestion process affects the rate at which foods are digested [5]. Therefore, clear attention should be given to the food matrix structure as well as to the food digestive process in order to understand how to control the glycemic index of carbohydrate-rich foods.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, it can be seen that the DH of bolus pools reached at the end of digestion are not significantly different between them, but they are slightly superior ( p = .04) to the DH obtained by the FSC and PP samples (Figure d and Table D in Appendix section). This could be attributed to the differences in the median particle size ( D 50 ) between the real (≈0.30 mm) versus artificial (≈0.45 mm) boli, as it is hypothesized a smaller particle size could enhance enzymatic hydrolysis analogous to what is seen for starch hydrolysis (Gao et al, ). However, in the same study, the starch digestion level was higher for the artificial as compared to the real boli, being attributed to their differences in hydration level, which were ≈20% higher in artificial boli.…”
Section: Resultsmentioning
confidence: 99%
“…To this extent, an international consensus for a harmonized static protocol based on physiologically relevant conditions in humans has been recently achieved during the INFOGEST cost action (Minekus et al, ). Recently, Gao et al () used this protocol to study the influence of the degree of breakdown of artificial and real bread boli produced ex vivo from human mastication. They found that more disintegrated boli had a higher starch hydrolysis rate.…”
Section: Introductionmentioning
confidence: 99%
“…Some research has been conducted on in vitro methods for studying the degree of in-mouth breakdown in relation to its impact on subsequent digestion. For example, a very recent study [27] using white bread compared four different in vitro oral processing methods (cutting with a knife, cutting and grinding with a pestle, blending, and grinding) to investigate the effect of fragmentation on bolus formation and on in vitro digestion. Another study [10] subjected pastas with different compositions to four different breakdown procedures (chewing by one volunteer, grinding / maceration, cutting with a knife, and cutting with a knife and grinding with a pestle) followed by in vitro gastric digestion.…”
Section: Discussionmentioning
confidence: 99%
“…One study of bread and spaghetti boluses obtained in vivo determined and compared the level of particle degradation and digestion before swallowing for each food [8]; the results highlighted the influence of oral digestion on the entire digestion process. In another recent study using white bread [27], different in vitro oral processing methods were applied to obtain boluses and their characteristics were compared with those of in vivo boluses; the kinetics of starch hydrolysis in the different boluses were also compared by performing in vitro gastrointestinal digestions.…”
Section: Introductionmentioning
confidence: 99%